Insect type material in the Laboratorio de Sanidad Vegetal, SENASA, Lima, Peru - Lozada, Pedro W. (2005)
A list of the type material of Insecta deposited in the Laboratorio de Sanidad Vegetal, Servicio Nacional de Sanidad Agraria (SENASA), Lima, Peru, presented here includes 21 species of Psylloidea (Hemiptera), 4 of Cicadellidae (Hemiptera), 4 of Curculionidae (Coleoptera), and 2 of Tachinidae (Diptera), all of them from Peruvian localities. The types of Tachinidae described by Charles Townsend have not been included in this list.